Dampak Belanja Pegawai, Belanja Barang, Belanja Modal dan Subsidi terhadap Realisasi Penerimaan Pajak di Indonesia - Nabila, Nabila; Rizal, Yani; Andiny, Puti; Fuad, Muhammad; Safrizal, Safrizal (Jurnal Samudra Ekonomi dan Bisnis, 2025)
The study analyzes the impact of employee spending, goods spending, capital spending, and subsidies on tax revenue realization in Indonesia. This study uses a quantitative approach based on secondary data from the Ministry of Finance of the Republic of Indonesia, and the analysis was conducted using the Error Correction Model (ECM) method with the help of Eviews 10. The results indicate that employee spending has no impact in the short term, but in the long term, a positive and significant impact was found on tax revenue realization. Goods spending in the short term has a negative and significant impact, while in the long term it has no impact on tax revenue realization. Capital spending shows a positive and significant impact in both the short and long term on tax revenue realization. On the other hand, subsidies do not have a significant impact on tax revenue in either the short or long term.